Peranan TKBM dalam Kegiatan Bongkar Muat pada PMB PT. Gelora Perkasa Belawan - Leonardo Purba; Masringgit Marwiyah Nst (Logistics and Supply Chain Insights, 2026)
This paper was written with the aim of analyzing the role of stevedoring workers (TKBM) in loading and unloading activities carried out by the Loading and Unloading Company (PBM) FT. Gelora Perkasa Belawan. In collecting data, the author utilized two approaches, namely field research and library research. Labor efficiency is a key factor in increasing operational productivity in the port sector, however, various problems are often found such as delays, low productivity, and work inefficiencies caused by weak monitoring and performance monitoring systems. In this study, a qualitative approach was used through field methods and library methods, on the operational activities of TKBM in the company. The results of the study indicate that the implementation of structured work and periodic evaluations can improve work discipline, accelerate loading and unloading times, and reduce operational costs. In addition, the role of management in providing constructive feedback and periodic training has also proven effective in supporting labor efficiency. Thus, optimizing the role of TKBM will have a direct impact on improving the performance of PBM PT. Gelora Perkasa Belawan, which ultimately contributes to the smooth flow of goods and economic growth in the Belawan port area.